Implementasi Green Chemistry Dalam Pembelajaran Kimia: Literatur Review - Shorihatul Inayah; I Wayan Dasna; Habiddin Habiddin (Universitas Pendidikan Mandalika Mataram, 2022)
Green chemistry in chemistry learning has been a central issue in chemistry education research the last ten years. The objectives of this literature review are: a) to map green chemistry research topics in chemistry learning the last ten years; b) to find out the opportunity for the implementation of Green chemistry in chemistry learning. The research method used is a systematic literature review of articles published in the scopus journal obtained from the Scopus database for the last 10 years (2011-2021). Article searches use titles, abstracts or keywords that meet logical conditions (